Thermogravimetry analysis, compressive strength and thermal conductivity tests of non-autoclaved aerated Portland cement–fly ash–silica fume concrete - Narattha C. (Springer Netherlands, 2015)
© 2015 Akadémiai Kiadó, Budapest, Hungary This paper reports the investigated thermogravimetry analysis, compressive strength and thermal conductivity tests of non-autoclaved aerated Portland cement–fly ash–silica fume concrete. The mixes were cured in water and air for 3, 7 and 28 days. Thermogravimetry results showed that calcium silicate hydrate (C–S–H), ettringite, gehlenite (C2ASH8), calcium hydroxide [Ca(OH)2] and calcium carbonate (CaCO3) phases were detected in all mixes. The compressive strength and thermal conductivity of aerated Portland cement–fly ash–silica fume concrete increased when compared with aerated Portland cement–fly ash concrete after 28 days. The compressive strength and thermal conductivity of aerated concrete cured in water had higher values than air-cured specimens. X-ray diffraction and thermogravimetry showed that Ca(OH)2 decreased with increased silica fume content. This is due to the increased pozzolanic reaction when compared with the Portland cement–fly ash mixes, which corresponds to an increase in compressive strength and thermal conductivity.